Effect of preheating and light-curing unit on physicochemical properties of a bulk fill composite - Theobaldo JD; Aguiar FH; Pini NI; Lima DA; Liporoni PC; Catelan A (Dove Medical Press, 2017)
Jéssica Dias Theobaldo,1 Flávio Henrique Baggio Aguiar,1 Núbia Inocencya Pavesi Pini,2 Débora Alves Nunes Leite Lima,1 Priscila Christiane Suzy Liporoni,3 Anderson Catelan3 1Department of Restorative Dentistry, Piracicaba Dental School, University of Campinas, Piracicaba, 2Ingá University Center, Maringá, 3Departament of Dentistry, University of Taubaté, Taubaté, Brazil Objective: The aim of this study is to evaluate the effect of composite preheating and polymerization mode on degree of conversion (DC), microhardness (KHN), plasticization (P), and depth of polymerization (DP) of a bulk fill composite.Methods: Forty disc-shaped samples (n = 5) of a bulk fill composite were prepared (5 × 4 mm thick) and randomly divided into 4 groups according to light-curing unit (quartz–tungsten–halogen [QTH] or light-emitting diode [LED]) and preheating temperature (23 or 54 °C). A control group was prepared with a flowable composite at room temperature. DC was determined using a Fourier transform infrared spectrometer, KHN was measured with a Knoop indenter, P was evaluated by percentage reduction of hardness after 24 h of ethanol storage, and DP was obtained by bottom/top ratio. Data were statistically analyzed by analysis of variance and Tukey’s test (α = 0.05).Results: Regardless of light-curing, the highest preheating temperature increased DC compared to room temperature on bottom surface. LED showed a higher DC compared to QTH. Overall, DC was higher on top surface than bottom. KHN, P, and DP were not affected by curing mode and temperature, and flowable composite showed similar KHN, and lower DC and P, compared to bulk fill.Conclusion: Composite preheating increased the polymerization degree of 4-mm-increment bulk fill, but it led to a higher plasticization compared to the conventional flowable composite evaluated. Keywords: composite resins, physicochemical phenomena, polymerization, hardness, heating